If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10m + -10 = -3 Reorder the terms: -10 + 10m = -3 Solving -10 + 10m = -3 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 10m = -3 + 10 Combine like terms: -10 + 10 = 0 0 + 10m = -3 + 10 10m = -3 + 10 Combine like terms: -3 + 10 = 7 10m = 7 Divide each side by '10'. m = 0.7 Simplifying m = 0.7
| -9t-4=5 | | 6x+9=69 | | 35=-5(2s+10) | | -8n+2=34 | | -6.1(3t+5)-2.2(4t-6)= | | 6x+1=-35 | | 10y+50=170 | | 10y+50=179 | | 0.75=not+0.6 | | 36=3v-10 | | 12(t-4)+6t=6(3t+3)-12 | | n-7n-10=n+3n+30 | | 54=2u+16 | | (-4)*(-3)= | | 3*(-3)= | | 3*(-3)*(-4)*(-3)= | | b^2-7b=18 | | 2x+8x-(6x+7)= | | 4x+15-15+3-8x=13 | | 5s^2-17s=6 | | 3x+4(x-8)-x=0.6(10x+15) | | x^2+6=150 | | -.33x+30=-x+10 | | 4x+8-6=3x-12 | | P-1(4)=p+2(2) | | 7.43x+9=55.2049+3x | | 27=d-18 | | .83x-.16=4 | | x/4=10 | | 3w+2=w+7 | | 25x=-625 | | 2x^4=-250x |